Sharia Financing Contracts on KPR Syariah iB Hebat Products at BPRS Dana Amanah Surakarta in the Perspective of Fatwa DSN-MUI - Sup, Devid Frastiawan Amir; Firdaus, Muhammad Irkham; Bilhaq, Aqil Mu’tashim (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This research aims to positions the current contract conditions as a basis for future contract development in KPR Syariah iB Hebat product at BPRS Dana Amanah Surakarta. This research uses qualitative, descriptive, and field research methods. The results is, KPR Syariah iB Hebat products at BPRS Dana Amanah Surakarta currently still use murabahah contracts, istishna' parallel contracts, and musyarakah mutanaqisah contracts. Therefore, along with the continued development of BPRS Dana Amanah Surakarta and increasing customer interest in KPR Syariah iB Hebat product, contract development has become a very important need to be able to accommodate customer needs. So, having various contract variations will give rise to many product variations, so that customers have more options to meet their needs for KPR Syariah iB Hebat products at BPRS Dana Amanah Surakarta.